2018
DOI: 10.4012/dmj.2017-036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface microtopography of titanium disks on cell proliferation and differentiation of osteoblast-like cells isolated from rat calvariae

Abstract: The surface topography of implant fixture is an important factor affecting the osseointegration. We herein demonstrated the effects of surface microtopography of titanium disks on proliferation and differentiation of osteoblast-like cells isolated from rat calvariae. Titanium disks with machine surface (MS), rough surface (R1) and rough surface combined with small cavities (R2) were used in an in vitro culture system. Rough surfaces (R1 and R2 disks) induced stronger osteoblast proliferation and differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The results seemingly indicate that adding roughness either has no affect or a slightly negative affect on osteoblast activity in contrast to past studies that assert that increasing roughness of titanium substrate enhanced cell proliferation or differentiation 15,29‐31 . However, many of these studies produce roughness via subtractive manufacturing, often using acid etching techniques which produce roughness on a smaller scale than was able to be produced in this study using additive manufacturing.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The results seemingly indicate that adding roughness either has no affect or a slightly negative affect on osteoblast activity in contrast to past studies that assert that increasing roughness of titanium substrate enhanced cell proliferation or differentiation 15,29‐31 . However, many of these studies produce roughness via subtractive manufacturing, often using acid etching techniques which produce roughness on a smaller scale than was able to be produced in this study using additive manufacturing.…”
Section: Discussioncontrasting
confidence: 73%
“…By focusing on surface roughness, this study evaluates the effect of surface roughness while minimizing confounding variables. In vitro studies have demonstrated that increasing the surface roughness of 3D printed titanium discs with acid etching between R a values of 0.29–3.26 μm significantly increased proliferation and activity of osteoblasts 15 . Micro and nano roughness is theorized to impact osseointegration by providing local asperities for osteoblast attachment, or by influencing the adsorption of proteins on the surface, inducing the expression of certain integrin, such as, α 2 β 1 , which in turn directly regulates osteoblast differentiation 16‐18 .…”
Section: Introductionmentioning
confidence: 99%
“…Blatt et al concluded in their study of early cellular response that the different surfaces of implants influence expression patterns in terms of proliferation, adherence, and differentiation in early osteoblastic maturation [51,52]. With regard to the surface obtained from the combination of blasting and acid passivation, several authors have suggested that when greater roughness is obtained, greater cell adhesion, and acceleration occurs in early osseointegration (first week) [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the roughness, other physical properties such as hydrophilicity also affect cell adhesion and growth [31,32]. Surface hydrophilicity is conducive to cellular attachment and proliferation on the surface [33].…”
Section: Discussionmentioning
confidence: 99%